A study of open-cell nickel-chrome metallic foam for an abradable compressor sealing - Lindop, Martyn (2015)
This thesis documents the investigation of open-cell Ni-Cr metallic foams, analysing the mechanical properties of the material as well as the properties of brazed samples. Also investigated was the effectiveness of an ultrasound non-destructive evaluation technique used to analyse braze quality.